IMPLEMENTASI MANAJEMEN HUBUNGAN MASYARAKAT DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI SEKOLAH MENENGAH ATAS NEGERI 12 WAJO - Ambo Upe; Sumarni; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of public relations management in increasing community participation at Wajo State Senior High School 12. The phenomenon of low community involvement in supporting school programs is the starting point for this study. Public relations management in schools is considered to have a strategic role in building harmonious communication, strengthening positive images, and opening up opportunities for collaboration between schools and communities. This study aims to comprehensively describe the implementation of public relations management in increasing community participation at State Senior High School 12 Wajo. The research method used was qualitative and descriptive, with data collected through interviews, observations, and document reviews involving the principal, teachers, public relations staff, school committee, and student parent representatives. Data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing/verification to obtain a comprehensive picture of the strategies, obstacles, and impacts of the implementation of public relations management in the school. The results of the study show that the implementation of public relations management in this school takes place through a relatively structured managerial cycle, starting from the planning stage, program implementation, to continuous evaluation involving various internal and external actors of the school. In addition, there are several factors that support the implementation of public relations management at SMA Negeri 12 Wajo. The main factors include participatory leadership from the principal, a clear public relations organizational structure, strong social capital within the community, effective internal communication, as well as support from parents and external partnerships. In addition to supporting factors, there are also findings of inhibiting factors. The main obstacle found is the socio-economic conditions of the community around the school, which are still diverse and mostly in the lower-middle category.